Model of Forming a Sharia Entrepreneurial Spirit In Islamic Boarding Schools - Afif, Ali; Febriati, Febriati; Dwi Widyastuti, Reni (Devotion : Journal of Research and Community Service, 2022)
Orphanages as places of learning and Islamic character building, have empowerment programs to help improve the quality of foster children's skills through formal education, religious education and entrepreneurship training. The purpose of this study was to analyze the strategies for encouraging entrepreneurial spirit in Islamic boarding schools and the factors that form the entrepreneurial spirit of students at Islamic boarding schools, especially in the Kubu Raya district, West Kalimantan province. The method used is behavioral observation, direct interviews with students and managers and caretakers at Islamic boarding schools. Then the results of the answers will be processed using triangulation data and to be concluded. The research was conducted at Mu'inul Islam and Darul Fikri Islamic boarding schools, Kubu Raya district, West Kalimantan province. The results of this study indicate that the main strategies and factors in building an entrepreneurial spirit are faith and piety. It was also found that Islamic boarding schools have a major role in molding Islamic entrepreneurial spirit, namely creating business units by empowering students and the community through entrepreneurship programs so that they can support and improve the welfare of students and the community in creating many jobs. Through the involvement of students in entrepreneurship in Islamic boarding schools, they have succeeded in educating alumni to establish business fields. namely creating business units by empowering students and the community through entrepreneurship programs so that they can support and improve the welfare of students and the community in creating lots of jobs. Through the involvement of students in entrepreneurship in Islamic boarding schools, they have succeeded in educating alumni to establish business fields. namely creating business units by empowering students and the community through entrepreneurship programs so that they can support and improve the welfare of students and the community in creating many jobs. Through the involvement of students in entrepreneurship in Islamic boarding schools, they have succeeded in educating alumni to establish business fields.